Voltammetric Behaviour of Two Stacking Layers of Copper-Bound 3-Mercaptopropionic Self-Assembled Monolayers on Gold Electrode and Application in Enhancement of Detection of Cu(II) - Phong, P.H.; Anh, N.H.; Hung, L.Q.; Ha, N.T.C.; Ha, V.T.T. (Asian Journal of Chemistry, 2012)
Formation of two stacking layers composed of copper-bound self-assembled monolayer (SAM) of 3-mercaptopropionic acid (MPA) for modifying the gold electrode has been studied by electrochemical method. Stack of self-assembled monolayers of 3-mercaptopropionic acid via a Cu(II) layer was elucidated by peak potentials and charge values obtained from cyclic voltammetry for reductive desorption of self-assembled monolayer in 0.5 M KOH solution. The attachment of Cu(II) layers to self-assembled monolayers was detected by differential pulse voltammetry with the appearance of a reduction peak at 0.18 V. This modified electrode has been successfully used for enhancing the sensitivity in determination of Cu2+ ions at picomolar concentration. The linear range obtained from 1.56 × 10-12-1.56 × 10-9 M with a correlation coefficient of 0.9962. The detection limit approached to 9.10 × 10-13 M. The electrochemical behaviour of the modified electrode was also obtained for speculating further formation and structure features.